2010
DOI: 10.1086/653489
|View full text |Cite
|
Sign up to set email alerts
|

In Cold‐Hardy Insects, Seasonal, Temperature, and Reversible Phosphorylation Controls Regulate Sarco/Endoplasmic Reticulum Ca2+‐ATPase (SERCA)

Abstract: Winter cold hardiness of insects typically involves one of two major strategies for survival below 0 degrees C: freeze avoidance and freeze tolerance. The two strategies have some common features, including the accumulation of high concentrations of cryoprotectant polyols and the frequent occurrence of diapause. Entry into the hypometabolic state of diapause requires coordinated suppression of major ATP-consuming metabolic processes, and ion motive ATPases are important targets for regulation. This study docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…As expected, the amount of 45 Ca 2+ accumulated in ER microsomes from the same preparation containing TG, was reduced by 70% with only 3142 ± 345 CPMs (2.16 nmol 45 Ca 2+ //min/mg protein). The difference in 45 Ca 2+ uptake between control and TG represented the TG-S SERCA activity and agreed with previous reports [6,25,27]. The final treatment was the addition of Ca 2+ ionophore A23187.…”
Section: Resultssupporting
confidence: 90%
“…As expected, the amount of 45 Ca 2+ accumulated in ER microsomes from the same preparation containing TG, was reduced by 70% with only 3142 ± 345 CPMs (2.16 nmol 45 Ca 2+ //min/mg protein). The difference in 45 Ca 2+ uptake between control and TG represented the TG-S SERCA activity and agreed with previous reports [6,25,27]. The final treatment was the addition of Ca 2+ ionophore A23187.…”
Section: Resultssupporting
confidence: 90%
“…Post‐translational modifications of proteins, such as reversible phosphorylation, provide one of the major mechanisms to suppress and reorganize metabolism in a coordinated and reversible manner during diapause and/or cold hardening without requiring major changes to overall protein levels via ATP‐expensive protein degradation or synthesis (Storey & Storey, ). The importance of protein kinase/phosphatase actions in cold survival by E. scudderiana was suggested from our earlier studies of the AMPK signalling pathway (Rider et al ., ) as well as the observed changes in phosphorylation states of various metabolic enzymes and ion channels during cold exposure of the larvae (Churchill & Storey, ; Muise & Storey, ; McMullen et al , ; Holden & Storey, ). Furthermore, it was demonstrated that temperature can serve as a trigger for various hypometabolic and cryoprotective adaptations on a molecular level (Ziegler et al ., ; Furusawa et al ., ; Storey & Storey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Crucial components of hypometabolic states such as diapause include the suppression of many energy expensive cell processes, while maintaining basal energy metabolism and enhancing cell preservation mechanisms (eg cyroprotectant synthesis, chaperones, antioxidants; Storey & Storey, ). Features of hypometabolism that have been documented to date in overwintering E. scudderiana include suppression of the activities of ATP‐dependent ion channels and mitochondrial enzymes (Joanisse & Storey, ; McMullen & Storey, ; McMullen et al , ), changes in enzyme function mediated by reversible protein phosphorylation (Muise & Storey, ; Holden & Storey, ) and seasonal adjustments of the activities of many metabolic and antioxidant enzymes (Joanisse & Storey, ; 1996). All of these are regulated by signalling pathways, particularly involving protein kinases and protein phosphatases, either acting directly to modify the function of proteins/enzymes or regulating transcription factors that control gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The Na + /K + -ATPase is known to play different roles in ionoregulation in different tissues, so it is not surprising that this enzyme may respond to a temperature change in different ways in different tissues. Nonetheless, this finding should be taken into consideration, particularly because whole animal samples have been used to test for a role of this enzyme in thermal adaptation and plasticity in insects in the past (MacMillan et al, 2015c;McMullen et al, 2010;McMullen and Storey, 2008), and this approach may obscure important patterns and thereby lead to erroneous conclusions on the mechanisms underlying thermal performance. For this reason, we recommend a tissue-specific approach be used whenever possible to address similar questions in the future.…”
Section: Discussionmentioning
confidence: 99%